Increasing the Community’s Economy Through Use of Processed Tomatoes - Nasution, Maria Ulfah; Alhifni, A (Journal of Islamic Economy and Community Engagement, 2020)
AbstractThe purpose of community service is done so that the community can utilize the potential of abundant natural resources (RNA) into a product innovation through training activities to make healthy snacks made from tomatoes, is expected to explore the potential of communities that have high selling points, so as to increase the income of the Kp community. Sirnagalih Padamulya Village. Indicators of achievement have a minimum understanding of managing abundant natural resources. The target of the Tom And Jelly making training program is the community of kp. Sirnagalih Padamulya Village, especially mothers. The method used in this community service is to use a workshop method (training) on the procedures for making products from processed tomatoes made into Tom And Jelly. The results of the community service activity were that the community was enthusiastic to know about tomato processing and were very motivated to become entrepreneurs, which can be seen from the many participants who wanted further action such as the grouping of Tom And Jelly businesses.Keywords: Training, Income Improvement, Tomato Utilization